Illiberalism and Constitutional Identity. A Critique from a Multilevel Perspective - Moș, Alexandru-George (Pécs journal of international and European law, 2023)
As democratic backsliding envelops Hungary and Poland, the legal authority of supranational actors becomes increasingly questioned. Among the legal arguments justifying their insubordi- nation, the two member-states of the European Union (EU) invoke the respect owed to national constitutional identity. The present work aims to prove that the use of constitutional identity as an excuse to overcome the primacy of EU law in the context of the rule of law crisis is unfounded. By approaching EU law from a multilevel perspective, the paper explores the roles, functions, and aims of constitutional identity and advances a theoretical test meant to identify uses of the concept which are compatible with EU law. By applying this test to the constitutional reality of Hungary and Poland, following their democratic backsliding, the paper argues that the language of consti- tutional identity is misused by the two EU member-states.